Effects of a 12-Week Semi-Immersive Virtual Reality-Based Exercise Program on the Quality of Life of Older Adults Across Different Age Groups: A Randomized Controlled Trial - Wang, Li-Ting; Wang, Yu-Wen (Applied sciences, 2025)
Aging may affect quality of life (QOL). This study aimed to evaluate the impact of semi-immersive VR-based exercise on the QOL of young-old and middle-old adults. This study was a randomized controlled trial involving older adults aged 65–85 years. Methods: Two age groups were each randomly assigned to experimental (EG) and control (CG) groups. The EG underwent a 75–90 min semi-immersive VR-based exercise intervention twice a week for 12 weeks, whereas the CG continued with their usual daily activities. Each participant’s psychological QOL was assessed using the World Health Organization’s QOL Instrument-Older Adults Module (WHOQOL-OLD). Results: Compared with their CG counterparts, the EG older adults exhibited significantly higher QOL scores in four WHOQOL-OLD dimensions (i.e., sensory abilities, autonomy, social participation/isolation, and death and dying) and had a superior overall QOL. Furthermore, we observed significant decreases in the autonomy and overall QOL dimensions in CG older adults. On comparing the young-old and middle-old adults, a significant decrease in the past, present, and future activity QOL dimension was exclusively found in CG young-old adults. Conclusions: Semi-immersive VR-based exercise is a promising digital tool for supporting the psychological QOL of older adults across different age groups. This suggests that older persons, particularly young-old adults, should be encouraged to maintain physical activity habits in their daily lives in order to improve their QOL.